Population Aging, Age Discrimination, and Age Discrimination Protections at the 50th Anniversary of the Age Discrimination in Employment Act - Patrick Button (Institute of Labor Economics (IZA), 2019)
This paper discusses population aging, increased participation of seniors in the labor force in the United States (and reasons for this), and how these trends are making the struggles of older workers in the labor market increasingly relevant. Evidence examining whether age discrimination is a barrier for seniors as they try to increase their work lives through the common practice of "bridge" jobs is also presented. After discussing the evidence that measures age discrimination, economics and legal research that seeks to determine to what extent the federal Age Discrimination in Employment Act and state-level age discrimination laws prevent age discrimination is discussed. In summary, current evidence indicates that age discrimination exists, but more so for older women. While evidence suggests that age discrimination laws may help, they cannot resolve the challenges imposed by population aging, especially for older women.
Keywords: J71; J78; J14; K31; J16; J26; 330; age discrimination; seniors; age discrimination in employment act; population aging; discrimination law; older women; sex-plus-age discrimination; intersectionality